2011
DOI: 10.3233/bmr-2011-0288
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Greek version of the Quebec Back Pain Disability Scale

Abstract: The Greek translation of the QBPDS provided reliable and valid instrument for the evaluation of Greek patients with low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…We found an excellent, significant correlation between the Hungarian versions of the ODI and QDS (r 0.81) which was similar to the previously published French (0.9) [17], English (0.82) [39] and (0.80) [14] and Polish (0.82) [23] versions of the questionnaires. Greek [31], Turkish [32] and Korean [34] studies reported weaker correlations between the ODI and the QDS (r: 0.78, 0.67 and 0.72, respectively). This study has several limitations which should be mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found an excellent, significant correlation between the Hungarian versions of the ODI and QDS (r 0.81) which was similar to the previously published French (0.9) [17], English (0.82) [39] and (0.80) [14] and Polish (0.82) [23] versions of the questionnaires. Greek [31], Turkish [32] and Korean [34] studies reported weaker correlations between the ODI and the QDS (r: 0.78, 0.67 and 0.72, respectively). This study has several limitations which should be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…The Cronbach-a for the whole scale was 0.95 which was almost the same as that published by Kopec et al for the original questionnaire (0.96). The factor structure of the final version of the QDS has been published previously by Christakou et al [31] only. They found that the items in the Greek version of the QDS loaded on six factors (movement, handling of large/heavy objects, bending/stooping, ambulation, sit/stand and bed/rest).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for the whole scale in these 5 studies ranged from .89 5 to .96. 5,16,17 We found moderate evidence for positive internal consistency of the English, French, Hungarian, and European Portuguese language versions of the QBPDS and limited evidence for positive internal consistency of the Greek and Turkish language versions. …”
mentioning
confidence: 88%
“…[1][2][3] It occurs in similar proportions in all cultures, interferes with quality of life and work performance, and is the most common reason for medical consultation. 4,5 To measure the construct of disability in patients with LBP, several self-report back-specific questionnaires have been developed. They are recommended by the World Health Organization as instruments to evaluate the efficacy of treatments.…”
mentioning
confidence: 99%